Farmers' Economic Dynamics: Challenges, Dependency, and the Role of Middlemen in the Agricultural System of Serdang Bedagai - Faiz Afza Ihsan; Anita Syamsinar; Ismail Ismail (Universitas Islam Negeri Sumatera Utara, 2023)
This study investigates the economic dynamics of farmers and the role of middlemen within the agricultural system of Serdang Bedagai, Indonesia. Using a qualitative case study approach, data were collected through unstructured in-depth interviews, field observations, and document analysis to explore the structural, economic, and institutional conditions shaping farmer livelihoods. The findings reveal that farmers experience multidimensional constraints, including dependency on middlemen for credit and market access, significant price asymmetry along the value chain, rising production costs due to limited access to subsidized inputs, unequal adoption of modern agricultural technologies, and persistent challenges in irrigation and local governance. These interconnected factors reinforce a cycle of vulnerability that limits farmers' bargaining power and economic mobility. The study highlights that farmers' dependency is not merely relational but structurally embedded within an environment of market failures and weak institutional support. The results contribute to agrarian political economy studies by demonstrating how market structure, infrastructure, and credit systems jointly reproduce dependency. Practically, the study offers insights for policymakers to strengthen agricultural infrastructure, expand access to formal credit, improve subsidy distribution, and promote inclusive technological transformation. The research concludes that comprehensive, multi-sectoral interventions are required to enhance farmer welfare and reduce structural dependency within rural agricultural systems